Health-related quality of life and its association with medication adherence in active pulmonary tuberculosis– a systematic review of global literature with focus on South Africa. Issue 1 (December 2016) - Kastien-Hilka, Tanja; Abulfathi, Ahmed; Rosenkranz, Bernd; Bennett, Bryan; Schwenkglenks, Matthias; Sinanovic, Edina
Abstract Introduction Tuberculosis (TB) is a leading cause of morbidity and mortality in South Africa. Clinical parameters are important objective outcomes in TB; however they often are not directly correlated with subjective well-being of the patient, but can be assessed using patient-reported outcome (PRO) measures. Health-related quality of life (HRQOL) is a specific PRO generally multi-dimensional in nature and includes physical, mental and social health domains. The inclusion of HRQOL PROs in trials and clinical practice can provide additional information beyondclinical and microbiological parameters. Furthermore, HRQOL may be associated with medication adherence. This review focuses on patient-reported HRQOL and its association with medication adherence in TB patients in South Africa. Methods A comprehensive search strategy was developed focusing on the impact of TB on patient-reported HRQOL, the existence of a conceptual framework of TB-specific HRQOL, determinants of medication adherence and the association of HRQOL with medication adherence. Data were extracted from all identified articles and additionaldata extraction was performed by two independent reviewers with special focus on longitudinal studies in order to understand changes of HRQOL and adherence over time. Research gaps were identified with regard to patient-reported HRQOL and medication adherence. Results A total of 66 articles met the eligibility criteria. Ten HRQOL studies and one adherence study used a longitudinal design, none of these in South Africa. A variety of different generic and disease-specific HRQOL measures were identified in the articles. In South Africa four HRQOL and five adherence studies (non-longitudinal) were published. Similar factors (socio-demographic, socio-economic, disease-related, therapy-related and psycho-social aspects) affect HRQOL and adherence. Although standard TB treatment improved all health domains, psychological well-being and social functioning remained impaired in microbiologically cured patients after treatment. Conclusion While evidence of TB impact on HRQOL and medication adherence and their association exists, it is verylimited for the South African situation. No valid and reliable TB-specific HRQOL measures were identified in this systematicreview. An assessment of HRQOL in TB patients in South Africa is required as this may assist with improving current disease management programmes, medication adherence and national treatment guidelines.